Menembus Batas, Melanggengkan Kerentanan: Aplikasi Teori Mezzadra dan Neilson terhadap Pekerja Migran Ilegal Indonesia di Belanda - Andi Zahra Sudirman (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
The phenomenon of undocumented Indonesian migrant workers in the Netherlands is a complex issue that is often viewed merely as an administrative problem or a failure of border control. This study aims to explain how structural mechanisms and Dutch migration policies systematically produce and perpetuate the vulnerability of these migrant workers in the informal sector. Using a qualitative-explanatory method, this study analyzes secondary data collected through a literature review using the theoretical framework of Sandro Mezzadra and Brett Neilson, which encompasses three interconnected concepts: “Border as method,” “Multiplication of labor,” and “Differential inclusion.” The findings reveal that strict immigration regulations such as the Compulsory Identification Act and the Koppelingswet do not function as absolute instruments of expulsion. Rather, these regulations operate as filtering mechanisms that deliberately produce “illegal” status to create a cheap, flexible labor force with minimal risk of social security claims. These exploitative conditions serve the needs of Dutch domestic capitalism to fill structural gaps in the informal labor market (shadow labor). On the other hand, the survival of these Indonesia’s migrants amid the absence of formal legal protection is heavily supported by social infrastructure in the form of Indonesian diaspora community networks, as well as the ambiguous role of public service professionals acting on humanitarian grounds. This study concludes that the unequal inclusion experienced by Indonesian migrant workers is not an administrative failure, but rather a consequence of global political-economic power relations maintained in the interests of capital.